Presbyterian reunion;: a memorial volume, 1837-1871 (Lent, 1871)
Historical review of the Church (Old School Branch) / by Samuel Miller -- Historical review of the Church (New School Branch) / by Jonathan F. Stearns -- Biographical sketches (Old School Branch) / by William B. Sprague --Biographical sketches (New School Branch) / by Z.M. Humphrey -- The reunion / by William Adams -- The assemblies of 1869 / by M.W. Jacobus -- Additional impressions / by P.H. Fowler -- The reconstruction / by G.S. Plumley -- The future church / by John Hall -- Statistics of the Church (Old School Branch) since 1837 / by David Irving -- Statistics of the Church (New School Branch) since 1837 / by Edwin F. Hatfield -- Brief sketches of the members of the reunion committee / by James H.M. Knox -- Documents, etc.